Social Empowerment Incubator: A Collaborative Model of Community Participation in Bandung - Sopandi, Encep; Hadi Kushendar, Deden; Habiburahman, Fadil (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
Social empowerment incubators play an important role in encouraging community participation and collaboration to drive sustainable social change. This study examines the development and implementation of a social empowerment incubator in Bandung, Indonesia, with a focus on its impact on community engagement, participatory governance, and collaborative networks. Using a qualitative approach with case studies, in-depth interviews, and participatory observations, this study explores how these incubators serve as catalysts for social innovation and local development. These findings highlight key success factors, challenges, and best practices in managing social incubators to empower marginalized communities. The study contributes to the discourse on social entrepreneurship and participatory governance by providing policy recommendations to improve the effectiveness of social incubators in urban environments